Respuesta :
Answer:
6
Step-by-step explanation:
To calculate x+10, we first need to find x. To do this, we can use the first equation.
We are given the equation:
[tex]x^2-8x=48[/tex]
To solve for x, turn one side of the equation into 0 and solve. Therefore:
[tex]x^2-8x=48\\x^2-8x-48=0\\(x-12)(x+4)=0\\x=-4, 12[/tex]
So, the possible values for x are -4 and 12.
However, we are also told that x<0. In other words, x must be negative. Thus, we can remove 12. That leaves us with: x=-4.
So:
[tex]x+10\\(-4)+10\\=6[/tex]
x^2 -8x - 48 = 0
(x-12)(x+4) = 0
x=12, x=-4
Since x<0, x must be -4
Therefore, -4+10=6
(x-12)(x+4) = 0
x=12, x=-4
Since x<0, x must be -4
Therefore, -4+10=6